On the Stock-Yogo tables - Christopher L. Skeels; Frank Windmeijer (Econometrics, 2018)
A standard test for weak instruments compares the first-stage F-statistic to a table of critical values obtained by Stock and Yogo (2005) using simulations. We derive a closed-form solution for the expectation from which these critical values are derived, as well as present some second-order asymptotic approximations that may be of value in the presence of multiple endogenous regressors. Inspection of this new result provides insights not available from simulation, and will allow software implementations to be generalised and improved. Finally, we explore the calculation of p-values for the first-stage F-statistic weak instruments test.
Keywords: C12; C36; C46; C52; C65; C88; 330; weak instruments; hypothesis testing; Stock–Yogo tables; hypergeometric functions; quadratic forms; p-values